Evidence for an intrinsic binding force between dodecaborate dianions and receptors with hydrophobic binding pockets. Issue 37 (18th April 2016) - Warneke, Jonas; Jenne, Carsten; Bernarding, Johannes; Azov, Vladimir A.; Plaumann, Markus
Abstract : Gas phase binding studies revealed strong intrinsic intermolecular interactions between dianionic dodecaborates [B12 X12 ] 2− and neutral organic hosts. Abstract : A gas phase binding study revealed strong intrinsic intermolecular interactions between dianionic halogenated closo -dodecaborates [B12 X12 ] 2− and several neutral organic receptors. Oxidation of a tetrathiafulvalene host allowed switching between two host–guest binding modes in a supramolecular complex. Complexes of β-cyclodextrin with [B12 F12 ] 2− show remarkable stability in the gas phase and were successfully tested as carriers for the delivery of boron clusters into cancer cells.